A study of sensory neural hearing loss in chronic suppurative otitis media - Upadhyay, Prakhar; Hiremath, Chandrashekharayya S.; Reddy K.R., Prasen (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
The role of chronic inflammatory disease of the middle ear as a cause of sensory neural hearing loss (SNHL) is still debatable. Therefore, the role of this study to see if there is a relation between SNHL and duration of chronic suppurative otitis media (CSOM), socio-economic (SE) status and age of patient. Methods: The hospital based case series study was conducted on all CSOM patients coming to ENT out-patient department in S. Nijalingappa Medical College and Hanagal Shri Kumareshwar (HSK) Hospital, Bagalkot, Karnataka over a period of one and a half years. After clinical examination, hearing evaluation was done using PTA as main tool. Results: Based on the present study, overall proportion of patients with SNHL was 20.66%. No relation of SNHL was found between sex and SE status of patient. No relation was found between severity of SNHL and age of patient. No relation was found between severity of SNHL and duration of CSOM. This present study shows that patients with CSOM with increased age have a greater chance of developing SNHL. Also, as the duration of CSOM increases there is a greater chance to develop SNHL. Conclusions: This study shows that the chance of developing SNHL in CSOM increases with age and disease duration. Hence, we can conclude that CSOM should be treated appropriately as early as possible to reduce the risk of developing SNHL in patients with CSOM.